1984
DOI: 10.1002/yd.23319842403
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for the severely disturbed mother

Abstract: Judith S. Musick is executive director of The Ounce of Prevention Fund in Chicago. Use of milieu and home‐nursing intervention strategies suggest some optimism in helping mothers of young children function better at home and in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…F. Cohn & Tronick, 1983;Downey & Coyne, 1990) and provide less stimulation (Field, 1992). Fathers are therefore less reciprocal, less involved, and less positive (Cohler, Gallant, Grunebaum, Weiss, & Gamer, 1980;Stott et al, 1984;Stott, Musick, Clark, & Cohler, 1983). Results of this study suggest that, as prior research on mothers has indicated, this is also the case for resident fathers in this sample.…”
Section: Symptoms Of Major Depression and Father Involvementmentioning
confidence: 46%
“…F. Cohn & Tronick, 1983;Downey & Coyne, 1990) and provide less stimulation (Field, 1992). Fathers are therefore less reciprocal, less involved, and less positive (Cohler, Gallant, Grunebaum, Weiss, & Gamer, 1980;Stott et al, 1984;Stott, Musick, Clark, & Cohler, 1983). Results of this study suggest that, as prior research on mothers has indicated, this is also the case for resident fathers in this sample.…”
Section: Symptoms Of Major Depression and Father Involvementmentioning
confidence: 46%
“…Mothers with an SMI have been accused of infecting the genetic pool and negatively influencing future generations (Apfel & Handel, 1993;Stott et al, 1984). Research concurs that having a parent with a mental illness increases a child's genetic vulnerability to psychiatric illness and behaviors (Mordoch & Hall, 2002;Sacker, Done, & Crow, 1996).…”
Section: Mothers With An Smi As Otheredmentioning
confidence: 96%
“…Through midlife, parenting issues are often intertwined with other stresses that themselves are likely to affect parenting adversely ( Cohler, Stott, & Musick, 1996 ; Stott, Mustek, Clark, & Cohler, 1983 ; Stott et al, 1984 ). A recent review of pregnancy and the postpartum period for North American mothers with SMI highlighted the stresses that both precede and co-occur with episodes of mental illness, and that continue after the episode resolves ( Mowbray et al, 1995 ).…”
Section: Motherhood In Contextmentioning
confidence: 99%